2005
DOI: 10.1016/s0002-9440(10)62260-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Prosurvival Signaling in Fibroblasts by a Protein Kinase Inhibitor Protects against Fibrotic Tissue Injury

Abstract: Inflammation and repair are stereotypical host responses to injury of adult mammalian tissues. Dysregulation of either of these processes may lead to pathological outcomes resulting in varying degrees of chronic inflammation and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 49 publications
2
113
0
2
Order By: Relevance
“…Stimulation of fibroblasts with endothelin-1 promotes enhanced contractile phenotype or activation, this is prevented by blockade of the PI3K/Akt pathway. 54 In agreement with this Vittal and colleagues 55 observed that inhibition of PKB/Akt in bleomycin-induced lung fibrosis markedly reduced accumulation of ␣-smooth muscle actin-expressing myofibroblasts.…”
Section: Discussionsupporting
confidence: 70%
“…Stimulation of fibroblasts with endothelin-1 promotes enhanced contractile phenotype or activation, this is prevented by blockade of the PI3K/Akt pathway. 54 In agreement with this Vittal and colleagues 55 observed that inhibition of PKB/Akt in bleomycin-induced lung fibrosis markedly reduced accumulation of ␣-smooth muscle actin-expressing myofibroblasts.…”
Section: Discussionsupporting
confidence: 70%
“…Our observations that the PI3K-AKT and integrin-FAK pathways are activated in a combinatorial manner by TGF-β1 to promote myofibroblast survival have important implications for broader understanding of dysregulated tissue repair and fibrotic diseases. Recent studies from our laboratory have shown that both FAK and AKT activation are increased in areas of active fibrogenesis following acute lung injury in mice [46]. Treatment with a protein tyrosine kinase inhibitor that blocks TGF-β1-activation of FAK and AKT in lung fibroblasts is protective against the development of fibrosis in this animal model [46].…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies from our laboratory have shown that both FAK and AKT activation are increased in areas of active fibrogenesis following acute lung injury in mice [46]. Treatment with a protein tyrosine kinase inhibitor that blocks TGF-β1-activation of FAK and AKT in lung fibroblasts is protective against the development of fibrosis in this animal model [46]. Additionally, we have shown that alveolar mesenchymal cells isolated from patients with non-resolving (fibrotic/persistent) acute respiratory distress syndrome (ARDS) demonstrate high levels of AKT activation and resistance to apoptosis compared to mesenchymal cells from patients with resolving ARDS [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is not known if restoration of fibroblast apoptosis can mitigate fibrotic lung disease in vivo, but several studies provide proof of principal that modulation of signaling pathways involved in fibroblast resistance to apoptosis can attenuate fibrogenesis in murine models (53)(54)(55)(56)(57). Our findings suggest that XIAP antagonists may have therapeutic potential in disease processes characterized by fibroblast accumulation and fibrosis, although it will be critical to determine the impact of these antagonists on other cell populations before translating this strategy to patient care.…”
Section: Discussionmentioning
confidence: 83%